2020
DOI: 10.1002/jsfa.10600
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pectinase‐assisted extraction of Annona muricata L. juice and the effect of liquefaction on its pectin structure

Abstract: BACKGROUND: Soursop (Annona muricata L.) is an underutilized tropical and subtropical fruit with high nutritional and therapeutic benefits. This fruit is faced with enormous post-harvest losses due to its high perishability. This work was aimed to optimize the pectinase-assisted extraction conditions of soursop juice using Doehlert design and to study the effect of pectinase on its pectin structure. RESULTS: The predicted models were validated for all the responses studied and the regression coefficients range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Gelling properties of pectin are determined by their degree of esterification and lies in the range of 60 to 90% (21) In previous studies, it was reported that the degree of esterification is affected by temperature (22) . Depending on the degree of proportion, pectin can be divided into two parts-rapid settings (DE> 72%), slow setting (DE,58-65%) (23)…”
Section: Degree Of Esterificationmentioning
confidence: 99%
“…Gelling properties of pectin are determined by their degree of esterification and lies in the range of 60 to 90% (21) In previous studies, it was reported that the degree of esterification is affected by temperature (22) . Depending on the degree of proportion, pectin can be divided into two parts-rapid settings (DE> 72%), slow setting (DE,58-65%) (23)…”
Section: Degree Of Esterificationmentioning
confidence: 99%
“…Pectin has a wide application prospect in the field of food because of its high abundance, the existence of functional components and excellent biocompatibility (Roy et al 2023). The application of enzyme treatment causes the removal of pectin methyl ester, leading to the breakdown of galacturonic acid bonds in pectin molecules (Makebe et al 2020). Figure 1 (a) showed that the pectin DE decreased rapidly for the first 60 min, which might be explained by the higher content of galacturonic acid in HMP at the initial stage of the reaction (Johansson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The application of enzyme treatment causes the removal of pectin methyl ester, leading to the breakdown of galacturonic acid bonds in pectin molecules (Makebe et al . 2020). Figure 1(a) showed that the pectin DE decreased rapidly for the first 60 min, which might be explained by the higher content of galacturonic acid in HMP at the initial stage of the reaction (Johansson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) indicated the improved contents and capacities of bioactive compounds in chokeberry juice with the addition of pectinolytic enzymes. Enzymatic liquefaction of other fruit juices such as apple and umbu (de Oliveira et al., 2018), blueberry (Siddiq et al., 2018), and soursop (Makebe et al., 2020) has also been reported.…”
Section: Introductionmentioning
confidence: 99%